Mentorship quality and mentors' work-to-family positive spillover: the mediating role of personal skill development and the moderating role of core self-evaluation. Issue 9 (15th May 2021) - Hu, Yiling; Wang, Minmin; Kwan, Ho Kwong; Yi, Jian
Abstract: This research examined the influence of mentorship quality on work-to-family positive spillover (WFPS) of mentors by focusing on the mediating role of personal skill development and the moderating role of core self-evaluations (CSEs). The findings based on a survey study of 187 formal Chinese mentors indicated that the positive linkage between mentorship quality and WFPS is mediated by personal skill development. In addition, the influences of mentorship quality on personal skill development is stronger for mentors whose CSE is high rather than low. These results evidence that a formal mentoring program has positive impacts on the family life of mentors in an Eastern setting.